Arginine enzymatic deprivation and diet restriction for cancer treatment (Brazilian Journal of Pharmaceutical Sciences, 2017)
Recent findings in amino acid metabolism and the differences between normal, healthy cells and neoplastic cells have revealed that targeting single amino acid metabolic enzymes in cancer therapy is a promising strategy for the development of novel therapeutic agents. Arginine is derived from dietary protein intake, body protein breakdown, or endogenous de novo arginine production and several studies have revealed disturbances in its synthesis and metabolism which could enhance or inhibit tumor cell growth. Consequently, there has been an increased interest in the arginine-depleting enzymes and dietary deprivation of arginine and its precursors as a potential antineoplastic therapy. This review outlines the most recent advances in targeting arginine metabolic pathways in cancer therapy and the different chemo- and radio-therapeutic approaches to be co-applied.